Lean production systems in the workplace / Ruzaidah A. Rashid ... [et al.] - A. Rashid, Ruzaidah; Muda Yusof, Nazuha; Mohamed, Zamzulani; Jaafar, Syaza Amira (2017)
The purpose of this study is to determine the relationships between top management commitment, communication and training and employees' awareness of Lean Production system at workplace. Moreover, the investigation of factors influencing employees' awareness of Lean Production system at workplace was done by analyzing three variables namely top management commitment, communication and training. The study was conducted at a car leather seat manufacturing company at Puchong, Selangor. From 156 respondents, it is found that all three variables showed the positive relationship towards employees' awareness of Lean Production system. Furthermore, the top management commitment is proved as the most influence factor of employees' awareness of Lean Production system as compared to training and communication factor. In order to ensure the effectiveness of Lean Production system, it is recommended to the top management to seriously embed the ongoing encouragement and enforcement of Lean Production system in the organization. The organization should also provide trainings to educate the employees and their role in the system.